Countercyclical Financial Regulation - Ren, Haocong (2012)
The global financial crisis has focused much attention on procyclicality, particularly in the context of a macroprudential framework. This paper reviews a set of prudential measures that can be adopted by national authorities to deal with procyclicality and discusses issues in designing and implementing such measures. For developing countries, in addition to some general considerations on policy design and implementation, a range of issues may warrant special attention. These include the balance between financial stability and financial development objectives, selection and calibration of policy instruments according to national circumstances and taking into account data limitations and capacity constraints as well as other practical challenges, and continued efforts to improve supervisory independence, supervisory powers and analytical capacity and to ensure adequate resources in order to perform the required tasks. Given the limited practical experience with countercyclical prudential measures, developing countries (as well as developed countries) will have to ascend a learning curve and experiment with select instruments while carefully monitoring and evaluating their effectiveness over time before a framework matures.